Oleocanthal Inhibits Catabolic and Inflammatory Mediators in LPS-Activated Human Primary Osteoarthritis (OA) Chondrocytes Through MAPKs/NF-κB Pathways - Morena Scotece; Javier Conde; Vanessa Abella; Veronica López; Vera Francisco; Clara Ruiz; Victor Campos; Francisca Lago; Rodolfo Gomez; Jesús Pino; Oreste Gualillo (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Oleocanthal (OC), a phenolic compound present in extra virgin olive oil (EVOO), has attracted attention since its discovery for its relevant pharmacological properties in different pathogenic processes, including inflammation. Here, we investigated the involvement of OC in LPS-activated osteoarthritis (OA) human primary chondrocytes. Methods: Human primary chondrocytes were harvested from articular cartilage samples obtained from OA patients. The effects of OC on the viability of chondrocytes were tested by MTT assay. Protein and mRNA expression of several catabolic and pro-inflammatory factors after OC treatment were measured by RT-qPCR and western blot respectively. Moreover, we analysed the NO production by Griess reaction. Finally, several pathways mediators were analysed by western blot. Results: We demonstrated that OC did not have any cytotoxic effect. Oleocanthal inhibited NO production and strongly decreased NOS2 and COX-2 protein and mRNA expression in LPS-activated human primary OA chondrocytes. Interestingly, OC also inhibits MMP-13 and ADAMTS-5. In addition, OC downregulates several pro-inflammatory factors, such as IL-6, IL-8, CCL3, LCN2 and TNF-α induced by LPS in human primary OA chondrocytes. Finally, we demonstrated that OC exerts its effects through the MAPK/P38/NF-kB pathways. Conclusion: These data show that OC is able to block LPS-mediated inflammatory response and MMP-13 and ADAMTS-5 induction in human primary OA chondrocytes via MAPKs/NF-kB pathways, suggesting that OC may be a promising agent for the treatment of inflammation in cartilage and a potential molecule to prevent disease progression by inhibiting metalloproteases and aggrecanases.